Tribological properties of calcium carbonate powders modified with Tween 40 as lubricant additives - Chen Tianhua (Functional Materials, 2017)
In this experiment, nanometer calcium carbonate was prepared by metathesis method. The nanometer calcium carbonate was modified by non-ionic surfactant-tween 40. The nanometer calcium carbonate before and after modification was analyzed and characterized by various methods. Scanning electron microscope (SEM) result show the size of the unmodified nano-calcium carbonate is about 200-400nm, while the particle size of the modified particles is about 200 nanometers. Contact angle indicate that CаCO₃ powders become hydrophobic after modified. Moreover the friction and wear properties of Tween 40-CаCO₃ as lubricant additives in rapeseed oil were evaluated with a four-ball friction and wear tester. Tween 40-CаCO₃ could improve the anti-wear and friction reducing capacities of rapeseed oil can conclude from the friction results. X-ray photoelectron spectroscope of worn steel surfaces indicated that an absorption film containing rapeseed oil and 40-CаCO₃ was formed.